2015
DOI: 10.3389/fpubh.2015.00273
|View full text |Cite
|
Sign up to set email alerts
|

African-American Women’s Perceptions and Experiences About Breastfeeding

Abstract: There are health benefits to breastfeeding for both mothers and their children. The preventive health effects of breastfeeding continue into adulthood, lowering rate of various chronic illnesses. African-American women, especially of lower socioeconomic status, are less likely to breastfeed in comparison to their racial and ethnic counterparts. The purpose of this study is to explore how African-American women experience breastfeeding in the early stages of postpartum care. Two focus groups (N = 20, 10 in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…In terms of maternal benefits, weight loss was a commonly mentioned motivator to breastfeed by women in this study. Obeng, Emetu, and Curtis (2015) also reported this as a health benefit mentioned by African American women in their focus group study. This is an important finding given not only the rates of obesity among African American women of reproductive age (Robbins et al, 2014) but also research on how gestational weight gain can affect women's health 18 years after birth (Holland, Groth, & Kitzman, 2015).…”
Section: Maternal Weight Loss As a Motivator To Breastfeedmentioning
confidence: 83%
“…In terms of maternal benefits, weight loss was a commonly mentioned motivator to breastfeed by women in this study. Obeng, Emetu, and Curtis (2015) also reported this as a health benefit mentioned by African American women in their focus group study. This is an important finding given not only the rates of obesity among African American women of reproductive age (Robbins et al, 2014) but also research on how gestational weight gain can affect women's health 18 years after birth (Holland, Groth, & Kitzman, 2015).…”
Section: Maternal Weight Loss As a Motivator To Breastfeedmentioning
confidence: 83%
“…This finding was consistent for parents from studies within all geographical regions, with the exception of two studies in which some mothers reported that breastfeeding (BF), in general, was not acceptable for infant feeding [59] or that colostrum was not considered appropriate [60]. Results from several studies indicated that parents believed that "breastfeeding is the natural way to feed infants" [34,47,56,61], or "the normal way to feed" [62], and that BF is the healthier option for infant milk feeding [41,55,63].…”
Section: Breastfeeding Is Best For An Infantmentioning
confidence: 95%
“…Parents desired professional and individualized instruction regarding infant feeding that was in keeping with their attitudes, beliefs, culture, and feeding decision from various sources [83], including physicians, pediatric nurses, lactation consultants, or professionals working in health care centers or public nutrition programs, described collectively here as health care providers (HCP). In contrast, studies illuminated that many parents found "infant feeding advice, support, and education from their HCP inadequate, missing completely, inconsistent or contradictory" [36][37][38]41,42,44,46,[49][50][51]53,55,57,63,72,74,76,83,97,98,103,104]. As identified within some studies, while it is important to promote and maintain BF, it is also necessary to ensure that the care, education, and needs of parents and their infants that are not BF are met [74,76], without stigmatizing parents who do not BF [68].…”
Section: Parent's Expectations Of Education and Support Addressing Pementioning
confidence: 99%
“… 44 A focus group study with black women found that breastfeeding was not mentioned during prenatal or postnatal care visits for some women, which contributed to their decision not to breastfeed their infants. 45 Participants suggested that prenatal breastfeeding education and supportive communication would help new mothers to breastfeed. Another study found that a brief counseling intervention that focused on providing information about the maternal health benefits of breastfeeding, including a lower risk of breast cancer, significantly increased breastfeeding intention among pregnant low-income black women (AOR=1.20, 95% CI=1.02, 1.42).…”
Section: Implications For Public Health Practicementioning
confidence: 99%